Fractional Calculus: From Theory to Applications (IntechOpen, 2025)
Over the last decade, research activity in the field of fractional calculus has surged, resulting in applications across a wide range of scientific disciplines. From the physics of diffusion and transport phenomena to control theory and financial systems, fractional calculus has proven valuable in numerous domains, capturing the interest of the scientific community. Therefore, this book comprises six chapters, each with the purpose of providing a brief overview of the subject of fractional calculus and its recent developments in theory and applications. This book aims to serve as an updated and handy reference for university professors, graduate students, laboratory researchers, as well as physicists and applied mathematicians who are interested in studying fractional calculus and its applications.